2017
DOI: 10.1002/app.44958
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonds prevent obtaining high molar mass PHUs

Abstract: Poly(hydroxyurethane)s (PHUs) are desired to replace PolyUrethanes (PUs) which are synthesized using harmful isocyanates. Nevertheless, the synthesis of PHUs starting from cyclocarbonates and amines displays two major drawbacks: the low reactivity observed during the opening of (poly)cyclocarbonates by (poly)amines and the low molar masses of polymers obtained. Currently, intensive work is carried out in order to increase the efficiency of the aminolysis of cyclocarbonates reaction but very few is dedicated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 48 publications
1
79
0
Order By: Relevance
“…Formation of hydrogen bonds : Recently, Blain et al. showed, through differential scanning calorimetry (DSC) and NMR spectroscopy, that low molar masses were not only due to the occurrence of side reactions, such as urea formation, but mainly due to hydrogen bonding . DSC reveals the presence of a second enthalpy of reaction, in addition to the enthalpy of reaction of the CC/amine system.…”
Section: Generalities Of Nipu Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of hydrogen bonds : Recently, Blain et al. showed, through differential scanning calorimetry (DSC) and NMR spectroscopy, that low molar masses were not only due to the occurrence of side reactions, such as urea formation, but mainly due to hydrogen bonding . DSC reveals the presence of a second enthalpy of reaction, in addition to the enthalpy of reaction of the CC/amine system.…”
Section: Generalities Of Nipu Synthesismentioning
confidence: 99%
“…[70] Formation of hydrogen bonds:R ecently,B lain et al showed, through differential scanning calorimetry (DSC) and NMR spectroscopy, that low molar masses weren ot only due to the occurrenceo fside reactions, such as urea formation, butm ainly due to hydrogen bonding. [17,71] DSC reveals the presence of a second enthalpy of reaction, in addition to the enthalpy of reaction of the CC/amine system.T his explains why full conversion of monomers cannot be reached, and thus, the low molar mass of PHUs. NMR spectroscopy and additional DSC analyses provide evidence that hydrogen bondingp lays ak ey role in PHU polymerization, andt he hydrogen-bonding network is mainly responsible for the second enthalpy of reaction.…”
Section: Side Reactionsmentioning
confidence: 99%
“…The reaction between cyclic carbonates and polyfunctional amines is the most promising method of obtaining these polymers. [11][12][13][14][15][16][17][18] The advantages of this synthesis over others are that contaminants are eliminated, toxic compounds are not used and carbon dioxide emissions are lower. In contrast to isocyanates, straight derivatives of cyclic carbonates such as, ethylene and propylene carbonate are non-toxic and biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…Methanol as byproduct of this reaction may enhance the conversion of 1, as mentioned in ref. where it was used as solvent. But as there are only slight amounts released, its influence is negligible.…”
Section: Resultsmentioning
confidence: 99%